2015
DOI: 10.1104/pp.15.00346
|View full text |Cite
|
Sign up to set email alerts
|

Different ROS-Scavenging Properties of Flavonoids Determine Their Abilities to Extend Shelf Life of Tomato

Abstract: The shelf life of tomato (Solanum lycopersicum) fruit is determined by the processes of overripening and susceptibility to pathogens. Postharvest shelf life is one of the most important traits for commercially grown tomatoes. We compared the shelf life of tomato fruit that accumulate different flavonoids and found that delayed overripening is associated with increased total antioxidant capacity caused by the accumulation of flavonoids in the fruit. However, reduced susceptibility to Botrytis cinerea, a major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 58 publications
2
57
0
1
Order By: Relevance
“…Various constitutive and induced plant phenolic compounds are thought to contribute to defense against microbial pathogens (Osbourn, 1996;Lattanzio et al, 2006), but not all phenolics have this effect (Henriquez et al, 2012;Zhang et al, 2015). In order to determine if flavan-3-ols have this function in planta, we screened five poplar genotypes for resistance against rust infection and quantified their phenolic contents.…”
Section: High Levels Of Catechin and Pas Are Associated With Resistanmentioning
confidence: 99%
“…Various constitutive and induced plant phenolic compounds are thought to contribute to defense against microbial pathogens (Osbourn, 1996;Lattanzio et al, 2006), but not all phenolics have this effect (Henriquez et al, 2012;Zhang et al, 2015). In order to determine if flavan-3-ols have this function in planta, we screened five poplar genotypes for resistance against rust infection and quantified their phenolic contents.…”
Section: High Levels Of Catechin and Pas Are Associated With Resistanmentioning
confidence: 99%
“…One significant feature of flavonoids is their high ROS-scavenging capacity, which is attributed to their ability to protect cells from oxidative damage under UV light, fungal infection, and insect herbivory (Clayton et al, 2018;Heim, Tagliaferro, & Bobilya, 2002;Stracke, Favory, et al, 2010;Zhang et al, 2013;Zhang et al, 2015). Defective flavonoid accumulation resulted in enhanced H 2 O 2 in plant tissues (Nakabayashi et al, 2014).…”
Section: Glycosidic Flavonoids Mitigate Ros Damage Under Osmotic Stmentioning
confidence: 99%
“…Defective flavonoid accumulation resulted in enhanced H 2 O 2 in plant tissues (Nakabayashi et al, 2014). Although flavonoids have been implicated in diverse biological processes (Gou, Felippes, Liu, Weigel, & Wang, 2011;Heim et al, 2002;Yang et al, 2016;Zhang et al, 2013;Zhang et al, 2015), the direct link between an individual isoform and its physiological effect on osmotic tolerance remains to be determined. This study shows that the SQD2.1-derived glycosidic flavonoids, in particular A7G, mitigate ROS accumulation and reduce oxidative damage under osmotic stress (Figures 8 and 9).…”
Section: Glycosidic Flavonoids Mitigate Ros Damage Under Osmotic Stmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study involving 24 apple varieties, correlation analysis revealed that phenols like flavonols and procyanidins B2 in the peel fraction of the inoculated fruit have a significant impact on blue mold resistance (Ahmadi-Afzadi et al, 2015). The comparison of tomato fruits that accumulate different levels of flavonoids and show different ripening behavior has also shed light on the role that specific flavonoids with high superoxide scavenging activities play in the higher resistance of some tomato lines to B. cinerea infection (Zhang et al, 2015).…”
Section: New Technologies For Studying Host-pathogen Interactions In mentioning
confidence: 99%